Preparation and In Vitro Characterization of Enoxaparin Nano-liposomes through Different Methods - Palassi, Sarveen (Adv Pharm Bull, 2021)
Purpose: Enoxaparin has been widely used as a choice drug for treatment and prevention of different coagulation disorders. Orally administered enoxaparin encounters with gastrointestinal barrier because of its high water solubility, high molecular weight and significant negative charge. Since, the nano-liposomes has gained great interest for oral drug delivery, we decided to introduce the best protocol for preparing enoxaparin nano-liposomes through in vitro characterization. Methods: Nano-liposomes were prepared by ethanol injection, thin film hydration, and double emulsion/solvent evaporation methods. Size distribution, zeta potential, loading efficiencies, and in vitro drug release of nano-liposomes were also studied. Results: The mean vesicle size was obtained under 100 nm, and the zeta potential was highly negative through all preparation methods. Nano-liposomes prepared by double emulsion/ solvent evaporation (DE) technique could entrap more of this hydrophilic drug (43 ± 7.1 %), but through thin layer hydration (TL) and ethanol injection (EI) only 28.4± 3.2% and 17.3 ± 2.5% of drug could be loaded into synthesized carriers. Drug release from these carriers was also obtained 42.17±1.72%, 29.43±0.34% and 32.27±0.14%, in 24 hours for EI, TL, and DE methods, respectively. Conclusion: Here, we can introduce double emulsion/solvent evaporation method as an acceptable method for enoxaparin loading, although some toxicity and in-vivo tests are also necessary to fully understand the potential of this formulation.